Destrubé family - photograph of Francette Destrubé at the grave of her Uncles, Guy and Paul, c. 1930, France (1930)
A photograph depicting Francette Destrubé (daughter of Georges and Suzanne) as a young child leaning on a headstone marking the grave of her uncles, Guy and Paul, who died during the Battle of Miraumont in the First World War.